Features of natural translation in a language testing environment. - Sherwood, Bianca. (University of Ottawa (Canada), 2000)
Natural translation (NT) environments reflect and shape participants' expectations and assumptions about translation activities. This study explores the features of NT environments with particular emphasis on a language testing environment. The data consists of samples of natural translations of a translation task which is a sub-test of a second language competence test for candidates seeking admission to a bilingual university program. In order to compare strategies, the same task was administered to student translators with two to three years professional training. The study also includes a translation of the test text by a fully qualified professional translator. The findings support the view that translating ability is a complex developmental cognitive competence. In performing the translation task, NT strategies tend to focus on a close linguistic matching of phrases. Student translators (STs), as is the case with the professional translator, appear to attend more systematically to a broader range of features including extra-linguistic factors. This attention to extra features may explain why most student translators were unable to complete the task in the allotted time. Nevertheless, the differences observed seem to be more a matter of degree than of type.
Keywords: Language, Linguistics.